EXAMINING THE CORRELATION OF SECONDARY SCHOOL’S COLLEGE COUNSELING SERVICE ON UNIVERSITY READINESS: A QUANTITATIVE STUDY - Zhumashov, Manas (Nazarbayev University Graduate School of Education, 2024)
This thesis examines the influence of college counseling services on university readiness among first and second-year university students. Utilizing a quantitative survey method, the study collected data from 60 participants across various universities in Kazakhstan and abroad, employing a mix of convenience and purposive sampling techniques. The research focused on assessing how counseling services contribute to aspects of university readiness such as academic preparedness and social integration. The findings indicated that students who actively engaged with college counseling services reported varied levels of readiness, highlighting significant differences based on whether students were attending universities domestically or abroad. Particularly, students aiming for education overseas exhibited higher engagement with counseling services but reported lower satisfaction levels, suggesting a potential mismatch between service provision and the specific needs of these students. Moreover, a substantial proportion of the student sample sought additional external support for university preparation, pointing to perceived gaps in the efficacy of school-provided services. This trend underscores a crucial demand for more specialized and personalized counseling approaches, especially for students pursuing education outside their home countries. The study acknowledges limitations including the small sample size and the non-random sampling method, which may affect the generalizability of the findings. Future research is recommended to involve larger, more diverse populations and to incorporate mixed methods to better capture the complexities of college counseling's impact on university readiness. This thesis may contribute to the understanding of the pivotal role of college counseling services and calls for enhanced strategies to better meet the diverse needs of students transitioning to higher education.
Keywords: Type of access: Open Access; college counseling and readiness; professional coordination; university readiness